A glimpse into the typologies of senior entrepreneurs / Dr. Marlina Muhamad, Dr. Fariza Hanis Abd Razak and Prof Dr. Haryani Haron - Ali Akbar, Yong Azrina; Abdul Razak, Fariza Hanis; Haron, Haryani (Universiti Teknologi MARA, Kedah, 2022)
Earlier research has examined the motivation of senior entrepreneurs, which is later reflected in the typology or also known as the types of senior entrepreneurs. A senior entrepreneur is defined as an elderly who has retired from previous employment to become a first-time ‘senior entrepreneur.’ The existing typologies of senior entrepreneurs are largely drawn from push and pull motivations driven by either extrinsic or intrinsic values. As time flies, the newly emerged motivations in senior entrepreneurship, have created up new and further studies in reflecting more typologies of senior entrepreneurs. The next section discusses the existing typologies of senior entrepreneurs, including the definition and characteristics of each typology.